Guided and quasiguided elastic waves in phononic crystal slabs - R. Sainidou; N. Stefanou (Physical Review B, 2006)
Guided and quasiguided elastic waves in a glass plate coated on one side with a periodic monolayer of polymer spheres, immersed in water, are studied by means of accurate numerical calculations using the on-shell layer-multiple-scattering method. This system supports, in addition to the modes of the bare plate, almost dispersionless, slow modes which originate from the array of spheres. We calculate and analyze in detail the dispersion diagrams of the interacting modes of the composite slab, and provide a consistent interpretation of the underlying physics.